Public Financing of Long-Term Care in Poland for the Elderly - Anna KONIECZNA (Communications of International Proceedings, 2020)
The aim of the article is to analyze the solutions of the Polish system of financing long-term care for the elderly. As part of the literature review, a short summary of the definitions of long-term care is presented, thus introduce its main essence. The diversity of the organization of long-term care services and their financing in Poland is the subject of a broader analysis of the financing of selected services in the scope of the entire health care system and life of society as a nation. The main focus was on the description of the Polish long-term care system, its organizational structure as well as the main principles and sources of financing. On the basis of the analysis of the Polish long-term care system, the issues concerning mainly the provision of benefits, their financing and availability were considered. The main difficulties in the functioning of the system were indicated, such as the lack of systemic legal regulations for all participants of the system, lack of coordination of activities, as well as dispersion of many sources of financing or the tasks of various benefits providers. As a summary was indicated the need for changes in the system, in particular towards the unification of rules and cooperation between entities and participants on many levels. The article presents the directions of changes in long-term care in Poland.
Keywords: Economy; Finance; Healthcare Management; Public Finance; Long-Term Care; Care Benefits.